The Diabetic Foot - Nather, Aziz (World Scientific, 2013)
This book provides a comprehensive guide for all healthcare professionals managing diabetic foot problems including general practitioners, nurses, podiatrists, orthopaedic surgeons, vascular surgeons and endocrinologists. It is also written in an easy to read fashion so that patients and caregivers will also find it useful. It covers a wide range of topics on the Diabetic Foot starting with an Introductory Section on "Overview of Diabetes". Topics include 'What is Diabetes?', 'Complications of Diabetes' and 'Management of Diabetes'. The section on "Basic Science of Diabetic Foot" covers Anatomy, Biomechanics and Pathogenesis: the Diabetes Foot Triad of Neuropathy, Vasculopathy and Immunopathy. Other Sections include Classification, Clinical Presentation and Treatment. A highlight of the book is the large "Guide to Operative Surgery" section. This section covers Major Amputations, Minor Amputation and other Diabetic Foot Surgeries. The latter details Surgical Debridement and Split Skin Grafting -- two of the commonest operations performed. This operative manual is also useful to residents and registrars.The section on Wound Care has also been carefully assembled to meet the needs of nurses, podiatrists and general practitioners, performing day to day dressing of diabetic wounds. It focuses on the use of New Generation Dressings including Silver and Iodine Dressings and Advances in Wound Healing. Patients and Care-givers will also find this useful.The last section "A Patient's Guide" is especially written to benefit patients and care-givers. It includes 'Care of Diabetes', 'Care of the Foot', 'Choosing your own Footwear', 'Doing your own Dressing' and 'Rehabilitating your Below Knee Amputation'.Finally, the Appendix includes details of the formation of NUH Diabetic Foot Team, Asia Pacific Association of Diabetic Limb Problems and the ASEAN Plus Expert Group Forum on the Management of Diabetic Foot Wounds.